ANALYSIS OF DERIVATIONAL PROSESS OF ENGLISH NOUNS FOUND IN THE JAKARTA POST ARTICLES - IRAWAN, RIYAN WIK (2007)
This research pa per is aimed at answering the three problems. The problems are: (1) What lexical categories are there in derivational process, and (2) What are the phonological conditions in the derivation process of English nouns. This research uses documentation and observation methods to get the data. The data are words taken from the articles on the newspaper. The writer concerns with three articles which are entitled: "Hamas PM urges unity deal with Abbas as truce holds","China preparing national plan for climate chan ge" and "Editor calls for democracy in china". To answer those problems, this research employs morphological analysis. The objectives are Identifying and analyzing the new derived words whether or not they have changed based on syntactical category. Analyzing the new derived words whether or not they have phonological changes based on phonological condition . The result of this study shows that first, there are some lexical categories that are changed into noun, the y are: derived lexical categories from verb and derived lexical categories from adjective. Second, there are phonological configurations in 14 bases in derivational process.